PENGARUH KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN PADA COUNTER ANDRIS RELOAD CELLULAR MADIUN - Alfian Sigit Permana (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This study aims to determine the quality of the product in Counter Andris Reload Cellular  Madiun,  to determine  the level  of customer  loyalty  in Counter Andris  Reload Cellular Madiun, and to know is there any effect of product quality on customer loyalty in Counter Andris Reload Cellular Madiun, The samples in this study using saturated sample as many 45 people without regard to existing strata in the population.  Data collection using questionnaires  and documentation. The research design used in this study was a descriptive correlational  design. In the statistical methods used to analyze the data with the regression formula and product moment  correlation. The results showed that the quality of products have influence at the same time a positive relationship to customer loyalty in Counter Andris Reload Cellular Madiun. It is derived from the value  of 0.724 while the value rcount and rtable 0.294 (0.724 > 0.294). By this means Ha acceptable product quality has a relationship with customer loyalty in Counter Andris Reload Cellular Madiun, It also obtained the value of the F test, Fcount at 47,372 while Ftable  of 4.06 (47,372 > 4.06). This means that there is rejection of HO which indicates that there are significant between product quality on customer loyalty in Counter Andris Reload Cellular Madiun. By this Ineans Ha received no difference between the effect of product quality on customer loyalty in Counter Andris Reload Cellular Madiun.